Labor induction information leaflets—Do women receive evidence-based information about the benefits and harms of labor induction? - von Dadelszen, Peter; Tohill, Susan; Wade, Julie; Hutcheon, Jennifer A.; Scott, Janet; Green, Marcus; Thornton, James G.; Magee, Laura A., the WILL Pilot Trial Study Group (Frontiers in Global Women's Health, 2022)
Objectives: To determine the extent to which a sample of NHS labour induction leaflets reflects evidence on labour induction. Setting: Audit of labour induction patient information leaflets - local from WILL trial (When to Induce Labour to Limit risk in pregnancy hypertension) internal pilot sites or national-level available online. Method: Descriptive analysis (n=21 leaflets, 19 [one shared] in 20 WILL internal pilot sites and 2 NHS online) according to NHS ‘Protocol on the Production of Patient Information’ criteria: general information (including indications), why and how induction is offered (including success and alternatives), and potential benefits and harms. Results: All leaflets described an induction indication. Most leaflets (n=18) mentioned induction location and 16 the potential for delays due to delivery suite workloads and competing clinical priorities. While 19 leaflets discussed membrane sweeping (17 as an induction alternative), only 4 leaflets mentioned balloon catheter as another mechanical method. Induction success (onset of active labour) was presented by a minority of leaflets (n=7, 33%), as “frequent” or in the “majority”, with “rare” or “occasional” failures. Benefits, harms and outcomes following induction were not compared with expectant care, but rather with spontaneous labour, such as for pain (n=14, with nine stating more pain with induction). Potential benefits of induction were seldom described (n=7; including avoiding stillbirth [n=4]), but deemed to be likely. No leaflet stated vaginal birth was more likely following induction, but most stated Caesarean was not increased (n=12); one leaflet stated that Caesarean risks were increased following induction. Women’s satisfaction was rarely presented (n=2). Conclusions: Information provided to pregnant women regarding labour induction could be improved to better reflect women’s choice between induction and expectant care, and the evidence upon which treatment recommendations are based. A multiple stakeholder-involved and evidence-informed process to update guidance is required.